On the Problem of Differentiation of Compound Words and Word-Combinations in English and Armenian - KARAPETYAN, SIRARPI (Bulletin of Yerevan University B: Philology, 2021)
The article concerns the problem of differentiating compound words and phrases in English and Armenian. It states the different criteria according to which many authors differentiate them: the phonetic criterion (that of the position of stress), the syntactic criterion, the semantic criterion (that of semantic cohesion), the criterion of formal-structural and functional integrity, etc. These criteria can serve as sufficient bases to differentiate between compound words and word-combinations only when taken collectively but not individually. In the article, parallels are drawn between English and Armenian, in the latter the borderline between word-combinations and compound words being far clearer.
Keywords: compound word, word-combination, criterion, stress, semantic, syntactic, structural, functional, integrity, Armenian, English